Clark W. Reynolds. The Mexican economy, twentieth century : structure and growth. New Haven : Yale University Press, 1970. 468 p. - Solís M., Leopoldo (Estudios Demográficos y Urbanos, 1972)
CLARK W. REYNOLDS, The Mexican Economy, Twentieth Century; Structure and Growth, New Haven, Yale University Press, 1970.